2021
DOI: 10.1111/ejn.15368
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of saving‐enhanced memory: Exploring similarities to list‐method directed forgetting

Abstract: People regularly outsource parts of their memory onto external memory stores like computers or smartphones. Such cognitive offloading can enhance subsequent memory performance, as referred to the saving‐enhanced memory effect (Storm & Stone, 2015). The cognitive mechanisms of this effect are not clear to date, however similarities to list‐method directed forgetting (LMDF) have been stated. Here, we examined in 52 participants the electrophysiological (EEG) correlates of the saving‐enhanced memory effect and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, offloading List B did not enhance recall for List A. Previous research has suggested that the saving-enhanced memory effect aligns with the phenomena of LMDF (Runge et al, 2020(Runge et al, , 2021Storm & Stone, 2015), such as the enhanced encoding explanation and the reduced interference at recall hypothesis (Bjork & Bjork, 1996). According to the first account, saving information frees cognitive resources, which would otherwise be utilized for rehearsing that information.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, offloading List B did not enhance recall for List A. Previous research has suggested that the saving-enhanced memory effect aligns with the phenomena of LMDF (Runge et al, 2020(Runge et al, , 2021Storm & Stone, 2015), such as the enhanced encoding explanation and the reduced interference at recall hypothesis (Bjork & Bjork, 1996). According to the first account, saving information frees cognitive resources, which would otherwise be utilized for rehearsing that information.…”
Section: Discussionmentioning
confidence: 77%
“…Speculations have been made about the mechanisms underlying the saving‐enhanced memory effect which parallel the phenomena of list method directed forgetting (LMDF; Runge et al, 2020, 2021), where cueing participants to forget a previously studied list (List A) and remember a new list instead (List B) also leads to the forgetting of the first list and enhanced memory of the second (see Bäuml et al, 2010; Sahakyan et al, 2013 for a review). Previous studies in the LMDF field have documented various processes that contribute to the memory enhancement effect.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is typically used in studies where access to offloaded information at test is not manipulated, as not explicitly mentioning the availability of notes at test may help to avoid the incorrect inference that the researchers will eventually take away notes at some later point in the experimental session. Moreover, similar lines of research (e.g., the savings enhanced memory effect) that permit participants to save information during encoding but do not permit the use of saved information at test have specifically instructed participants when notes will be available for restudy before the test but not during the test (Bohay et al, 2011;Runge et al, 2019Runge et al, , 2021Storm & Stone, 2015). That is, rather than specifying whether offloaded information will be available at test, researchers tend to provide explicit instructions only when offloaded information will not be available at test.…”
Section: Encoding Phasementioning
confidence: 99%
“…Speculations have been made about the mechanisms underlying the saving-enhanced memory effect which parallel the phenomena of list method directed forgetting (LMDF; Runge et al, 2020Runge et al, , 2021, where cueing participants to forget a previously studied list (List A) and remember a new list instead (List B) also leads to the forgetting of the first list and enhanced memory of the second (see Bäuml et al, 2010;Sahakyan et al, 2013 for a review). Previous studies in the LMDF field have documented various processes that contribute to the memory enhancement effect.…”
Section: Introductionmentioning
confidence: 99%